An Evaluation of Indonesian Capital Market Co-integration with ASEAN 4 to Enter the ASEAN Capital Market Integration in Accordance to ASEAN Economic Community (AEC) 2020 Scheme: Should Indonesia Enter or Postpone? - Suryanta, Barli (The Indonesian Capital Market Review, 2011)
Association of South East Asian Nations (ASEAN) Economic Community (AEC) 2020 has already been declared on 7 October 2003 by ASEAN Concord II in Bali, Indonesia. In general, AEC was designed to prepare ASEAN countries for ASEAN economic integration within the next 10-15 year. ASEAN Free Trade Area (AFTA) had actually been launched since 1992 though was not comprehensive enough and kept ASEAN only partially integrated. To overcome it, ASEAN proposed inancial integration through capital market integration based on AEC commitment in order to reach comprehensive ASEAN economic integration. Indonesia is one of the ASEAN members that is linked by AEC 2020. The purpose of this paper is to evaluate Indonesian capital market co-integration in entering the ASEAN capital market integration compared to those of ASEAN 4. To examine the notion of the Indonesian capital market integration within ASEAN region, cointegration model is utilised to igure out co-integration between Indonesian stock market indices and ASEAN 4, i.e., Singapore, Malaysia, Philippines and Thailand. In addition, Vector Auto-regression (VAR) model is also utilised to examine Indonesian market returns co-movement and dynamic link with ASEAN 4. The conclusions of this research, i.e. co-integration between Indonesian capital market with Singaporean, Malaysian, Philippines, and Thailand does not exist; there is neither co-movement nor strong dynamic link between Indonesian capital market with those of Singaporean, Malaysian, Philippines, and Thailand. This paper also recommends Indonesia to postpone the integration of its capital market into the integrated ASEAN capital market.